Stakeholder co-creation during the innovation process: Identifying capabilities for knowledge creation among multiple stakeholders - Kazadi, Kande; Lievens, Annouk; Mahr, Dominik (Journal of business research, 2016)
Extant research investigates a firm’s ability to manage co-creation with one type of stakeholder during the innovation process, rather than co-creation with multiple stakeholders simultaneously. While such stakeholder co-creation creates benefits for the focal firm such as access to unique resources and knowledge bases, it also raises new challenges because of the diverse characteristics, interests and goals of the different stakeholders involved. Specific capabilities to anticipate and manage these challenges are therefore of particular interest for research and practice. The study here narrows this gap by conducting an in-depth case study, examining multiple stakeholder co-creation projects embedded within a pharmaceutical firm. The study develops a contingency framework on the role of four stakeholder co-creation capabilities in generating valuable knowledge. Overall, these findings complement extant literature by examining how specific capabilities employed before and during the innovation project may explain differential performance of stakeholder co-creation activities.